A checklist of aquatic nematodes from Cuban Archipelago - Pérez-García, José Andrés; Ruiz-Abierno, Alexei; Armenteros, Maickel (Zootaxa, 2020)
The diversity of free-living aquatic nematodes is largely unknown for the Gulf of Mexico and Caribbean Sea. The Cuban Archipelago is an important part of this because of its large area and diversity of habitats. We analyzed the free-living nematodes from 83 sites from seven aquatic habitats around Cuba, to produce a checklist for many habitats, including seagrass meadows, coral degradation zones, algal turf, bare sands, unvegetated muds, freshwater and anchihaline caves, and deep-sea sediments. The checklist contains 469 species, 229 genera, 50 families, and 9 orders. Chromadorida, Enoplida, and Monhysterida were the best represented orders with 112, 100, and 83 species respectively. The most abundant species were Euchromadora vulgaris, Terschellingia longicaudata, Desmodora pontica, Sabatieria pulchra , and Epsilonema sp. Most of the listed species were new records for the region. There were differences in the number of species recorded in each habitat type, with seagrass meadows having 280 species, coral degradation zones having 139 species, deep waters having 116 species, algal turf having 114 species, bare sands having 100 species, unvegetated muds having 78 species, freshwater caves having 19 species, anchihaline caves having 16 species, and freshwater streams having 6 species. The checklist is the most comprehensive recent report of the diversity of free-living nematodes in the regions of Gulf of Mexico and Caribbean Sea. The reported diversity is higher than many other regional checklists likely reflecting the intense sampling effort and the variety of microhabitats in Cuban Archipelago.